Overview of the Mars climate station for Tianwen‐1 mission. Issue 4 (18th August 2020) - Peng, YongQing; Zhang, LeiBo; Cai, ZhiGuo; Wang, ZhaoGang; Jiao, HaiLong; Wang, DongLi; Yang, XianTao; Wang, LianGuo; Tan, Xu; Wang, Feng; Fang, Jing; Sun, ZhouLu; et al.
Abstract : The background and scientific objectives of the Mars Climate Station (MCS) for Tianwen‐1 are introduced, accompanied by a comparative review of the status of related meteorological observation missions and of advanced sensing technologies. As one of the China Tianwen‐1 Mission's principal scientific payloads, the MCS contains four measurement sensors and one electronic processing unit that are specially designed to measure local temperature, pressure, wind, and sound on the Martian surface. The MCS's measurement principles, technical schemes, ground calibration techniques, and adaptability evaluation to the Mars surface environment of MCS are introduced in details. The conclusion presents measurement performance specifications of the MCS, based on ground test results, that will provide guidance to future research based on data from the Tianwen‐1 and later Mars missions.